Diseño de un plan de mejoramiento de selección de personal en el departamento de Gestión de Talento Humano del Hospital de Clínicas Pichincha - Rojas Rojas, María Fernanda (2013)
This thesis project raises the issue Design an improvement plan in the selection process of the Department of Human Resource Management of Pichincha Clinic`s Hospital, located in Quito city. We start with a diagnosis of the problem, identifying the causes and effects that originate from the current process. This leads to the immediate search for a solution, for which it is proposed the need for a new process, which determine the procedures for selection of personnel in the area of human talent, which it will meet the basic objective that is to attract, develop and keep talent with the skills required by the company.